Peranan TNF-a dalam Patofisiologi Skiatika Akibat Hernia Nukleus Pulposus dan Pendekatan Terapi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Conventionalconcept about sciatica is a radicular compression of sciatic nerve due to disk herniation. Nevertheless the role of chemicalfactors were performed by some experts based on several reasons such as thefact that disk operation can not aleviate the pain, large disk herniation not alwaysfollowed by symptoms, severe pain does not always show any prove of compression on imaging, severity of the symptoms and neurological deficit does not always related to the extent of disk herniationvand conservative treatment mostly effective overtime. Sciatica is a condition of low backpain radiated to the leg associated with the clinical signs of radicular iritation (positive straight leg test),painfelt radicular inpattern and may/may not be associated with neurological deficits. Pathophysiology of sciatica: (1) compression cause ischemia, edema, and demielinisasi on DRG and radix, (2) Evidence of immuneprocess involvement: herniated disk is concerned as aforeign body that elicits spontaneous autoimmune inflammation response whichproduces pain, including Nitric oxide (NO),pro-inflammatory cytokines (TNF,IL-I, IL-6, IL-8), Cyclooxigenase-2 (COX-2),phospholipaseA2, tromboxane,leucotriens,prostagiandinE2 (PGE2), and increased level of matrix metalloproteinase (MMPs) which plays an important role in the release process ofbioactive TNFinto the extracellularfluid and causes cartilago damage and inhibitsproteoglican biosynthesis. TNF is a proinflammatory cytokine which starts other cytokine cascade, and growth factors as immune response. The main effect ofTNF-a consists of upregulation on MMP and gen expression, cytokines stimulation such as ILl, IL-6, IL-8, inflammatory mediators such as PGE2, stimulation of cellular migration, disturbe endothelial permeability, decrease in collagen proteoglican synthesis and produce hyperalgesia due to inflammation. Anti- TNF-a is a biologic agent consists of' the chimeric monoclonal IgG I antibody infliximab with human constant and murine variable regions: the recombinant 75kD TNF receptor IgGl fusion protein etanercept: the jillly humanized monoclonal antibody adalimumab. TNF-a inhibitor can prevent theformation of thrombus, intraneural edema and reduction in nerve conduction velocity.